A new species of Australotaenia (Cestoda: Proteocephalidae) from a hylid frog in Australia - Chambrier, Alain DE; Scholz, Tomáš (Zootaxa, 2024)
A new species of the little-known genus Australotaenia de Chambrier & de Chambrier, 2010 is described from Ranoidea australis (Gray) (Anura: Hylidae), commonly known as the giant frog, northern snapping frog or round frog and which is a burrowing frog species native to Australia. Australotaenia hobbsi n. sp. is the fourth species of the genus, but the first taxon found in a burrowing frog and in northern Australia. The other species were found in Australian tree frogs (Litoria spp.) in southwestern and southeastern Australia, and in the homalopsid snake Enhydris enhydris (Schneider) in Cambodia. Australotaenia hobbsi n. sp. differs from its congeners (i) by the wider strobila (maximum body width 1,750 µm versus < 930 µm), scolex (570 µm versus < 390 µm) and suckers (diameter 215-230 µm versus < 140 µm); (ii) by the smaller relative size of the cirrus sac (12-15% of proglottid width versus 17-33%); (iii) by the absence of a vaginal sphincter (present in the other three species); (iv) different arrangement of the inner longitudinal musculature, which consists of a few individual muscle fibres (in contrast to the fibres grouped in bundles in other species). Australotaenia species and Pangasiocestus romani Scholz & de Chambrier, 2012 from the spot pangasius Pangasius lernaudii Boucourt, both of the subfamily Acanthotaeniinae, are unique among proteocephalids in terms of intermediate uterine development, with a high concentration of chromophilic cells around the tip of the lateral uterine diverticula.
Keywords: Body Size; mužské pohlaví; velikost těla; rozšíření zvířat; žáby; Organ Size; velikost orgánu; ženské pohlaví; Austrálie; zvířata; anatomické struktury zvířat; Animal Distribution; Cestoda; Australia; Anura; Female; Animal Structures; Male; Animals